Histo-architectural Variation in the Teat of Sheep and She Goat - Modekar, Shilpa S.; Dhande, P.L. (Indian Journal of Veterinary Anatomy, 2023)
The present study was carried out to compare histoarchitecturalvariation if any, present in the teats of the sheep and she goat in their lactating and non-lactating stage. The study revealed that in both the small ruminants, teat wall comprised of skin, fibro-musculo vascular layer and teat mucosa from outside to inside. Skin was made of layers of epidermis and dermis. Epidermal layer comprised of stratified squamous keratinised epithelium whereas dermal layer comprised of hair follicles, nerve endings, sweat glands and sebaceous glands. The first layer which is the most outer layer is the normal skin formed from epidermis and dermis has few number of fine hairs usually associated with clusters of sebaceous glands surrounding the hair follicles. The hair were completely absent at the middle and tip of the teat. The third layer (most inner layer) was the epithelial lining of the teat sinus and teat orifice. The teat sinus was lined by two layer of cuboidal cells which got converted in to stratified squamous keratinize at the teat orifice. Teat cistern and Furstenberg’s rosette was lined by a bilayered cuboidal epithelium. There was remarkable variation in the thickness of teat skin epidermis, epithelial height of teat canal, and keratin and pre-keratin layers thickness in lactating and non-lactating ewes and she-goats.